Control del gusano taladrador del fruto (Diaphania nitidalis l.) del pepino (Cucumis sativus L.) aplicando bioinsecticidas en la zona de Quevedo. - Arellano Fernández, Ardían Jamín (2013)
This research was carried out in the grounds of the La Maria. Located Km.5 via Splice, Province of Los Ríos. Geographical coordinates 79 28 'west longitude and 01 06' south latitude, at an altitude of 120 meters. It raised the overall objective: Identify the specific biocide doses to control borer worm in growing cucumber and specific: a) Determine the effectiveness of biocides in the yield of cucumber crop b) Analyze the treatments being studied economically , subject to the hypothesis: Applying biocides in cucumber cultivation rationally handled worm control fruit borer. The treatments were Neem (1.5 L ha-1), Snuff (1.5 L ha-1), Nettle ((2.0 l ha-1), Biopirosil ((1.0 L ha-1) and control without application. was used to design randomized complete block with five treatments in four replications. All study variables were subjected to analysis of variance and comparison of treatment means was used to test Tukey 95% chance to establish the statistical difference between treatments. A higher insect population in the control treatment compared to treatments that were dosed with organic controls, especially since the third week of the applications made. The presence of the insect caused problems in several variables subject to study, mainly on the number of sheets which was much lower in the control treatment. additionally affect other production variables, noticing that dosed treatment with organic controls showed greater plant height, weight , diameter, fruit length and yield (kg ha-1) especially in the treatment of Neem which was superior to the other controls used. Applying the bio-insecticides, to control the incidence of insect improved growth performance, Neem especially so obtained the higher income. Keywords: bio-insecticides, pepper, borer worm